Diagnostic Performance of FibroTouch Ultrasound Attenuation Parameter and Liver Stiffness Measurement in Assessing Hepatic Steatosis and Fibrosis in Patients With Nonalcoholic Fatty Liver Disease - Qu, Ying (Clin Transl Gastroenterol, 2021)
INTRODUCTION: To evaluate the diagnostic performance of ultrasound attenuation parameter (UAP) and liver stiffness measurement (LSM) by FibroTouch for diagnosis of hepatic steatosis and fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). METHODS: We recruited 237 patients undergoing FibroTouch and liver biopsy within 2 weeks. The pathological findings of liver biopsy were scored by Nonalcoholic Steatohepatitis Clinical Research Network, and the diagnostic accuracy of UAP for steatosis and LSM for fibrosis was evaluated by area under the receiver operating characteristic curve (AUROC). The impacts of histological parameters on UAP and LSM were analyzed, and diagnostic performance of FibroTouch UAP and LSM was compared with other noninvasive biomarkers. RESULTS: The success rate of FibroTouch examination was 96.51%. The AUROC of UAP for diagnosis of steatosis ≥S1, ≥S2, and S3 was 0.88, 0.93, and 0.88, and the cutoff values were 244, 269, and 296 dB/m, respectively. The AUROC of LSM for the diagnosis of fibrosis stages ≥F2, ≥F3, and F4 was 0.71, 0.71, and 0.77, and the cutoff values were 9.4, 9.4, and 11 kPa, respectively. Multiple regression analysis showed that LSM was positively correlated with degree of fibrosis and NAFLD activity score. UAP was positively correlated with liver steatosis. The diagnostic performance of UAP for steatosis was significantly superior to that of the hepatic steatosis index. DISCUSSION: FibroTouch has a low failure rate with moderate to high diagnostic performance for discriminating the steatosis degree and fibrosis stage and is suitable for clinical evaluation and monitoring of patients with NAFLD.